Common bacteria isolated from skin wounds of saltwater crocodile (Crocodylus porosus) - Panes, Teresita S.; Abrazado, June F.; Molina, Elizabeth C. (2011)
The main objective of the study was to investigate the presence of common bacterial contaminants in the skin wounds of saltwater crocodile and isolate and identify these common bacterial genera. Three (3) crocodiles with skin wounds were sampled from which a total of 20 skin wounds were swabbed for isolation of the common organism. Identification of the individual colonies was based on morphological, cultural, and staining reactions. Conventional biochemical tests were used in the characterization of the organism and Analytical Profile Index 20E was used for the identification of the isolates. Among the 13 individuals colonies selected and subjected to API 20E, seven Gram-negative organisms were identified. These were Serratia marcescens, Klebsiella pneumoniae spp pneumoniae, Enterobacter cloacae, Aeromonas hydrophila, Onchrobactrum anthropi, Proteus vulgaries, and Proteus mirabilis.
Keywords: Crocodiles; Mindanao studies